Application of the Weld Deposits on Function Surfaces of the Forest Machines Components - Kalincová, Daniela; Ťavodová, Miroslava; Ľuptáčiková, Veronika (Manufacturing Technology Journal, 2018)
The abrasive wear of pulley surfaces at winding of the ropes causes changes of the shape and quality surface of the groove and has influenced lifetime of the skidding machine. The pulley is made of steel C45E without heat treatment and its structure is not suitable for the abrasive wear of the pair metal-metal. Contribution describes a research aimed to changes in material structure by the heat treatment. The pulleys (first one in original state and second one after heat treatment) were tested in operating load at skidding during 320 hours. After experimental test, measurable properties as weight loss, groove dimensions of the pulleys were compared. On the samples from the pulleys, material resistence to wear was tested too. Another alternative for change of material properties would be an aplication of various types of weld deposits on the steel C45E. We have examined the quality of weld deposits and compared their hardness and microstructure. The results of experimental tests resulted to recommendations for practice.
Keywords: pulley; resistence to wear; weld deposit; microstructure; hardness